The importance of patient perspectives in pulmonary hypertension - McGoon, Michael D.; Ferrari, Pisana; Armstrong, Iain; Denis, Migdalia; Howard, Luke S.; Lowe, Gabi; Mehta, Sanjay; Murakami, Noriko; Wong, Brad A. (The European respiratory journal, 2019)
The assessment of objective measurement of cardiopulmonary status has helped us achieve better clinical outcomes for patients and develop new therapies through to the point of market access; however, patient surveys indicate that more can be done to improve holistic care and patient engagement. In this multidisciplinary review, we examine how clinical teams can acknowledge and embrace the individual patient's perspective, and thus improve the care for individual patients suffering from pulmonary hypertension by cultivating the importance and relevance of health-related quality of life in direct clinical care. At the individual level, patients should be provided with access to accredited specialist centres which provide a multidisciplinary approach where there is a culture focused on narrative medicine, quality of life, shared decision making and timely access to palliative care, and where there is participation in education. On a larger scale, we call for the development, expansion and promotion of patient associations to support patients and carers, lobby for access to best care and treatments, and provide input into the development of clinical trials and registries, focusing on the patients’ perspective.